Efektivitas Penerapan Model Pembelajaran Reciprocal Learning (RL) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran SKI Di Kelas VIII MTsS Thawalib Gunung Padang Panjang - Rika Nurhasanah; Laili Ramadani; Zulfikri Zulfikri (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research was motivated by the large number of students who scored below the KKM in the History of Islamic Culture subject at MTsS Thawalib Gunung Padang Panjang class VIII. To help solve this problem, researchers are interested in trying out a Reciprocal Learning learning model to improve student learning outcomes. This learning model will enable students to help students so that they are able to jointly use rational thinking skills and emotional awareness, to understand feelings, values, attitudes and behavior patterns. This research was conducted from November 8, 2023 to December 18, 2023. This research was an experimental study with a Randomized Control Group Posttest Only Design. The population in this study was class VIII MTsS Thawalib Gunung Padang Panjang. The sample was selected purposively from a certain population. Researchers chose class VIII C as the experimental class, and class VIII A as the control class. The instrument used is a test. To test the research hypothesis, the researcher used the t-test and processed the data using SPSS. Based on data analysis, the tcount results are greater than ttable. tcount is 3.180 and ttable is 1.679 with the average value of the experimental class being 84.38 and the control class being 72.57. So it can be concluded that the Reciprocal Learning learning model is effective on student learning outcomes in the Islamic Cultural History subject.